2019
DOI: 10.1042/bsr20190126
|View full text |Cite|
|
Sign up to set email alerts
|

Resveratrol attenuates inflammation environment-induced nucleus pulposus cell senescence in vitro

Abstract: Intervertebral disc degeneration is a disease identified as an inflammation response-participated pathological process. As a classical cellular feature, disc cell senescence is reported to be closely related with disc cell senescence. Resveratrol has a protective role against inflammation in some cells. However, its biological effects on disc cells remain largely unclear. The present study was aimed to study the effects of resveratrol on disc nucleus pulposus (NP) cell senescence in an inflammation environment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(68 citation statements)
references
References 34 publications
1
50
0
Order By: Relevance
“…To investigate the accurate role of inflammation in mediating disc degenerative changes, many researchers carried out studies in this field. Specifically, several studies have demonstrated that interleukin-1β increases NP cell apoptosis ratio or sensitizes NP cell to certain pathological factors-mediated cellular apoptosis [20,[28][29][30][31][32][33][34]. Similarly, there are evidence that TNF-α is also an inductive factor to cause unwanted NP cell apoptosis [24,35].…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the accurate role of inflammation in mediating disc degenerative changes, many researchers carried out studies in this field. Specifically, several studies have demonstrated that interleukin-1β increases NP cell apoptosis ratio or sensitizes NP cell to certain pathological factors-mediated cellular apoptosis [20,[28][29][30][31][32][33][34]. Similarly, there are evidence that TNF-α is also an inductive factor to cause unwanted NP cell apoptosis [24,35].…”
Section: Discussionmentioning
confidence: 99%
“…So, in terms of RSV, there is no need to doubt its therapeutic impact on IDD because there have been plenty of studies demonstrating that in the past. However, nearly all of them have described the mechanism from the view of inhibiting the downstream pathways that have already been activated by IL-1β or TNF-α (8,9,16). We de nitely do not deny that, but we want to explain the therapeutic mechanism from a novel angle, which is IL-6 and the JAK/STAT3 pathway, the reason why we have concentrated on them and established meaningful ndings.…”
Section: Discussionmentioning
confidence: 99%
“…The anti-in ammatory, anti-cancer, anti-aging, and chondrocyteprotective effects of RSV have been demonstrated previously by many studies (10)(11)(12)(13). Recently, various researchers have shown that RSV can attenuate the deleterious effects on the intervertebral disc caused by external pathological factors, such as high glucose, IL-1β, and TNF-α (9,(14)(15)(16). It has been demonstrated that RSV can effectively mitigate cell senescence and apoptosis, and can even alleviate the in ammation response caused by the aforementioned factors by regulating different signaling pathways, such as the PI3K/AKT, extracellular regulated protein kinases 1/2 (ERK1/2), and reactive oxygen species/nuclear factor kappa beta (ROS/NF-κB) pathways (8,14,17,18), thus impeding IDD.…”
Section: Introductionmentioning
confidence: 89%
“… 164 In vitro, resveratrol partially counteracted the inflammatory effects of TNF-α and IL-1β, including decreased ECM content and increased NP cell senescence and matrix degradation enzymes (MMP-3, MMP-13, and ADAMTS-4). 165 Resveratrol also showed a similar anticatabolic effect to reverse the matrix degradation and apoptotic induction of oxidative damage caused by hydrogen peroxide in NP cells. 166 The effect may be mediated by the activation of autophagy 165 through the PI3K/Akt pathway 167 or AMPK/SIRT1 signaling pathway 168 but does not seem to involve the MAP kinase pathways or the NF-κB/SIRT1 pathway.…”
Section: Molecules Under Laboratory Investigation To Target Inflammatmentioning
confidence: 94%